Occurrence of virulence factors and antimicrobial resistance in Pasteurella multocida strains isolated from slaughter cattle in Iran - Khamesipour, Faham; Momtaz, Hassan; Azhdary Mamoreh, Morteza (Frontiers in Microbiology, 2014)
A total of 30 Pasteurella multocida strains isolated from 333 pneumonic and apparently health slaughter cattle were examined for capsule biosynthesis genes and 23 virulence associated genes by polymerase chain reaction. The disc diffusion technique was used to determine antimicrobial resistance profiles among the isolates. Of the isolates, 23 belonged to capsular type A, 5 to capsular type D and two isolates were untypeable. The distribution of the capsular types in pneumonic lungs and in apparently health lungs was statistically similar. All virulence genes tested were detected among the isolates derived from pneumonic lungs; whereas isolates derived from apparently health lungs carried 16 of the 23 genes. The frequently detected genes among isolates from pneumonic lungs were exbD, hgbA, hgbB, ompA, ompH, oma87 and sodC; whereas tadD, toxA and pmHAS genes occurred less frequently. Most of the adhesins and superoxide dismutases; and all of the iron acquisition and protectin proteins occurred at significantly (p≤0.05) higher frequencies in isolates from pneumonic lungs. Isolates from apparently healthy lungs didn’t carry the following genes; hsf-1, hsf-2, tadD, toxA, nanB, nanH and pmHAS. One adhesion (hsf-1) and two iron acquisition (exbD and tonB) genes occurred at significantly (p≤0.05) higher frequencies among capA isolates. All the P. multocida isolates were susceptible to ciprofloxacin, co-trimoxazole, doxycycline, enrofloxacin, nitrofurantoin and tetracyclines. Different proportions of the isolates were however resistant to ampicillin, amoxicillin, erythromycin, lincomycin, penicillin, rifampin, streptomycin and florfenicol. Our results reveal presence of virulence factors in P. multocida strains isolated from symptomatic and asymptomatic bovids. A higher frequency of the factors among isolates from symptomatic study animals may suggest their role in pathogenesis of P. multocida-associated bovine respiratory disease. The results further reveal occurrence of an